Peran Media Sosial dalam Pembentukan Opini Publik dan Dinamika Kebijakan Pemerintah di Era Digital - Duvalio Adnan Zordi; Mohammad Syahrul Ihsan; Muhamad Aprian Nazarudin; Tria Patrianti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The 21st century is marked by a profound transformation in digital communication. Social media has become a new public space, enabling people to interact, disseminate information, and shape public opinion rapidly and massively. This article analyzes the role of social media in shaping public opinion and its influence on the dynamics of government policy in Indonesia. Through a literature review and case analysis of policies influenced by viral issues on social media, this study finds that social media increases citizen participation and accelerates government responses to public issues. However, the pattern of 'viral-based policy' also carries risks, such as reactive policies, a lack of evidence-based policies, and inequality in representation. To manage this phenomenon, the government needs to develop an inclusive digital communication strategy, establish an early detection system for public sentiment, and uphold the principles of good governance and evidence-based policy. These findings are relevant for academics and policymakers seeking to understand the interaction between social media, public opinion, and government policy in the digital era.